Existence and Uniqueness of Best Proximity Points for Generalized Almost Contractions - Chirasak Mongkolkeha; Chayut Kongban; Poom Kumam (Abstract and Applied Analysis)
The purpose of this paper is to elicit some interesting extensions of generalized almost contraction mappings to the case of non-self-mappings with α-proximal admissible and prove best proximity point theorems for this classes. Moreover, we also give some examples and applications to support our main results.